A DNA walker powered by endogenous enzymes for imaging uracil-DNA glycosylase activity in living cells. Issue 43 (7th May 2019) - Xu, Xiaowen; Zhang, Pingping; Zhang, Ruiyuan; Zhang, Nan; Jiang, Wei
Abstract : A DNA walker powered by endogenous enzymes detects uracil-DNA glycosylase activity in living cells. Abstract : A DNA walker powered by endogenous enzymes is constructed. It performs automatic walking in living cells and can detect the uracil-DNA glycosylase activity in situ .